Just War And Perpetual Peace: A View On Kants’ Position - Charles B. Berebon; Dinebari Vareba (dialektika kontemporer, 2022)
“War” and “peace” are perhaps the most speculative bipolar notions in human history. Since the dawn of human civilization, “Mother Earth” has faced constant conflict between war and peace. Theoretical analysis of the ideas of “war” and “peace” has been undertaken by intellectuals and philosophers from the dawn of time in an attempt to resolve this tension. In this work, it is discovered that Immanuel Kant made a genuine effort to establish the causes of and justification for war. An esoteric examination of Kantian Practical Philosophy indicates that Kant offers a novel type of “Just War Theory.” In the meantime, Kant seeks adequate solutions to the question, “What actions should be adopted after war?” How do we eliminate the likelihood of future wars? How may we achieve an everlasting state of peace? In this paper, we will examine Kant's perspectives on these questions. This work investigates further to determine if “just war theory” and “determining the methods for eternal peace” are incompatible. This work is separated into four portions. In the first part, we shall examine just war theory and its underlying ideas. In the second part, we shall examine Kant as an opponent of just war theory. In the third part, we portray Kant as a just war theorist, while section four examined the consistency between just war theory and Kant's concept of perpetual peace.